2015
DOI: 10.1007/s10597-015-9887-z
|View full text |Cite
|
Sign up to set email alerts
|

Coping Styles Among Individuals with Severe Mental Illness and Comorbid PTSD

Abstract: There is little known about coping styles used by individuals with severe mental illness (SMI) and even less known about the influence of a comorbid posttraumatic stress disorder (SMI-PTSD) diagnosis on coping. The current study examines differences in utilization of coping strategies, overall psychological distress, and exposure to traumatic events between SMI only and SMI-PTSD individuals seeking community mental health clinic services (N = 90). Results demonstrate that overall psychological distress and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 119 publications
(260 reference statements)
1
8
0
Order By: Relevance
“…[2] Additionally, PTSD symptoms correlated with dysfunction in daily living, depression, anxiety, impulsive behavior, relationships, and psychosis, consistent with research suggesting PTSD compounds difficulties for patients with SMI. [2,7,9] Though the majority of patients reported elevated PTSD symptoms, only 5.3% of the total sample received a primary or secondary diagnosis of PTSD, supporting previous findings of PTSD's possible under-diagnosis in this population. [13,14] However, further analyses indicate complexity in the diagnostic landscape of an inpatient setting.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…[2] Additionally, PTSD symptoms correlated with dysfunction in daily living, depression, anxiety, impulsive behavior, relationships, and psychosis, consistent with research suggesting PTSD compounds difficulties for patients with SMI. [2,7,9] Though the majority of patients reported elevated PTSD symptoms, only 5.3% of the total sample received a primary or secondary diagnosis of PTSD, supporting previous findings of PTSD's possible under-diagnosis in this population. [13,14] However, further analyses indicate complexity in the diagnostic landscape of an inpatient setting.…”
Section: Discussionsupporting
confidence: 76%
“…While exposure to trauma does not guarantee the development of PTSD symptoms, individuals with SMI also have a higher number of overall trauma exposures than individuals without SMI, and amount of cumulative trauma exposure relates to the presence and severity of PTSD symptoms in patients with SMI. [6] Patients with both SMI and PTSD symptoms report greater severity of psychological distress and slower recovery than both patients with SMI alone [2,7] and patients with SMI and trauma exposure but no PTSD symptoms. [8] Research has supported models which propose PTSD symptoms interact with SMI and increase the severity of SMI symptoms in patients who have experienced trauma, [8][9][10] yet in many treatment settings, recognition and treatment of PTSD is secondary to management of SMI symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have demonstrated that coping style is related to psychological outcome among individuals who have experienced trauma [34,35]. Furthermore, Bonanno and his team found that deficits in coping flexibility were indicative of pathology in bereaved individuals [36].…”
Section: Discussionmentioning
confidence: 99%
“…PTSD itself negatively affects the course of SMI. The study by McNeill et al [27] also showed that patients with PTSD in SMI have increased avoidance coping which leads to significant psychological distress and a more highly taxed psychiatric state. After stressful events, those with SMI and PTSD are at greater risk of engaging in life-endangering behaviors, and are at greater danger of attempting suicide than those with SMI alone [28].…”
Section: Discussionmentioning
confidence: 99%